Dimensi SERVQUAL Pada Kualitas Layanan Satpol PP Kota Dumai Dalam Penertiban ODGJ - Rusnita, Widya Cancer; Persada, Adlin (Jurnal Administrasi dan Kebijakan Publik, 2024)
Dumai City is one of Indonesia’s strategic regions, characterized by complex social dynamics, including the management of people with mental disorders (ODGJ). This study aims to analyze the service quality of the Dumai City Civil Service Police Unit (Satpol PP), motivated by the increasing number of ODGJ disrupting public order, particularly in strategic locations, and the challenges faced by Satpol PP in addressing these issues. This research employs a qualitative method with data collection techniques, including observation, in-depth interviews, and document analysis. The study utilizes the SERVQUAL approach, which encompasses five dimensions: reliability, responsiveness, tangibles, empathy, and assurance. The findings reveal that in terms of reliability, while Satpol PP has consistently responded to public reports following established procedures, the absence of standardized operational procedures (SOP) and specialized training presents significant challenges. Regarding responsiveness, the unit demonstrates commendable responsiveness; however, limited personnel and the absence of personal protective equipment (PPE) hinder operational efficiency. The tangibles dimension highlights that while operational facilities, such as vehicles, are adequate, supporting equipment like restraints and PPE remains highly limited. The empathy dimension shows that persuasive and humane approaches have been applied, although training related to empathy is insufficient. Finally, the assurance dimension indicates effective inter-agency coordination, albeit not optimal during non-working hours.The study recommends enhancing the quality of Satpol PP services in managing ODGJ through the development of clear SOPs, increased training programs, improved inter-agency collaboration, and better resource allocation. These improvements are expected to enable Satpol PP to handle ODGJ effectively, safely, and humanely, thereby increasing public trust in government institutions